PENGARUH PENDAPATAN BUNGA DAN KREDIT SIMPAN PINJAM TERHADAP SISA HASIL USAHA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) SATU JUNI SMK N 1 METRO - Lestari, Winda Rika; Ni’mah, Ghina Rahmatun (Jurnal Manajemen dan Keuangan, 2008)
Koperasi Pegawai Republik Indonesia (KPRI) Satu Juni is the one of cooperation that work in the unity of solve and borrow money. The condition of SHU it self that consist in Koperasi Pegawai Republik Indonesia (KPRI) Satu Juni at last two years had a decreasing, this case happened because the income of loan it self and credit of solve and borrow money that distributing is decrease.If looked the condition that happened in Koperasi Pegawai Republik Indonesia (KPRI) Satu Juni, there for the writer expose one of the important case that looked in what side the real condition of the biggest income of the loan and credit of solve and borrow the money give influence in rest of the final result of works.The hypothesis that showed by the writer are how big the income of loan and credit of solve and borrow money have a positive influence and significant in rest of the result.The analysis tools that used in this case result by using analysis program SPSS are the regression analysis tool, double linier, and double of correlation of coefficient.After calculate the result and discussion, therefore the final result that income of loan with r hitung 0,903 > r table 0,878 have positive relation in rest of the result and of the credit of solve and borrow money have positive relation and that things have a strongest of the relation r = 0,973. if looked big in F hitung sebesar 20,383 > Ftabel = 19,00 or significant 0,047 < 0,05, With that condition can said there is a significant of influence between income of loan and credit of solve and borrow money in rest of result.It is better if cooperative more care in rest of the final result that gotten from the important income for paying an activity of cooperative. More little the capital and donation that have more difficult to passing credit of solve and borrow money which distributed by cooperative. key word: income of loan and credit of solve and borrow money (KPRI) Satu Juni.